Analisis Kemampuan Komunikasi Matematis Siswa Ditinjau dari Gaya Berpikir Gregorg pada Materi Relasi dan Fungsi - Rahmia Rahmia; Muliana; Amam Taufiq Hidayat; Fajriana (FKIP Universitas Palangka Raya, 2025)
Students' low mathematical communication skills indicate obstacles in conveying and understanding mathematical ideas, both verbally and in writing. This study aims to analyze students' mathematical communication skills according to Gregorc's thinking style on the topic of relations and functions. The method used was descriptive qualitative, with data collected through a thinking style questionnaire, a mathematical communication test, and semi-structured interviews. Four eighth-grade students were purposively selected, each representing one type of Gregorc's thinking style. The study's findings indicate that students with an abstract sequential thinking style achieve coherent, logical, and complete mathematical communication, while those with a concrete random thinking style tend to have difficulty conveying ideas systematically. It is concluded that thinking style influences students' mathematical communication styles, so teachers need to consider differences in thinking styles in developing effective lesson plans.